Empirical Research on Data Science Talent Training and Enterprise Demand in Colleges and Universities - Dai, Jinhua; Su, Kun (Pacific International Journal, 2022)
The advent of the information age has given rise to a huge amount of data, and it becomes crucial to use the data well and bring its value into play. How colleges and universities train data science talents to meet the huge demand of the industry is of great significance. In this paper, the demand information of data science talents from recruitment websites was crawled by a typical web scraper and then carried out pre-processing, statistical analysis, and visual display. Through fully excavating the job information and summarizing the law of enterprise demand, constructive suggestions were put forward for data science talent training in colleges and universities, providing a reference basis for talent training units to develop training programs.